Hsa_circ_0000106 Acts as a Tumor Promoter in Pancreatic Cancer by Targeting the MiR-455–3p/HDAC4 - Hao, Shunxin; Yao, Zhi; Liu, Yifeng (Hormone and Metabolic Research, 2023)
Circular RNAs (circRNAs) frequently participate in pancreatic cancer (PC) progression. This study focuses on circ_0000106, a novel circRNA, and its potential function in PC development. Circ_00001106, miR-455–3p, and HDAC4 expression levels in PC were determined using qRT-PCR and immunoblotting. RNA immunoprecipitation and dual-luciferase reporter assays were performed to verify their binding interactions. Loss-of-function assays, including CCK-8, colony formation, and transwell assays, were used to estimate the proliferative and migratory properties of PC cells. A nude mouse model was constructed to assess the influence of circ_0000106 on tumor formation in vivo. A pronounced elevation of circ_0000106 and HDAC4 and a reduction of miR-455–3p in PC were observed. Circ_0000106 was prone to binding to miR-455–3p, and miR-455–3p further targeted HDAC4. Functionally, the proliferative and migratory properties of PC cells were dampened by the loss of circ_0000106 or HDAC4 and could be potentiated by miR-455–3p inhibition. Moreover, the knockdown of circ_0000106 delayed tumor growth in vivo. Additionally, the downregulation of miR-455–3p attenuated the repressive effects of circ_0000106 deficiency on PC cell migration and proliferation. Loss of HDAC4 exerted similar mitigative effects on miR-455–3p downregulation-stimulated PC cells. In conclusion, circ_0000106 promotes tumor migration and growth in PC by targeting the miR-455–3p/HDAC4 axis. These results suggest that the circ_0000106/miR-455–3p/HDAC4 network could be regarded as a latent target for PC treatment.
Keywords: pancreatic cancer; circ_0000106; miR-455–3p; HDAC4; proliferation; migration